Captain America Vol. 1, Stand - Straczynski, J. Michael, 1954- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2024)
"Decades ago, Steve Rogers changed the world forever. Now, powerful and insidious forces are assembling to ensure he never does it again. Past, present and future collide as the Sentinel of Liberty reckons with an existential threat determined to set the world on a darker path--at any cost! So the last thing Steve needs is for Spider-Man to crash date night seeking help foiling the Sinister Six's latest plot! Meanwhile, more and more of Captain America's former enemies are being recruited by a mysterious entity--one seemingly connected to a foe Steve faced long before he picked up the shield. And when Misty Knight uncovers a string of murders with seemingly supernatural origins, something strikes Cap as familiar"--